Antiglutamate Receptor Antibodies and Cognitive Impairment in Primary Antiphospholipid Syndrome and Systemic Lupus Erythematosus - Gerosa, Maria; Poletti, Barbara; Pregnolato, Francesca; Castellino, Gabriella; Lafronza, Annalisa; Silani, Vincenzo; Riboldi, Piersandro; Meroni, Pier Luigi; Merrill, Joan T. (Frontiers in Immunology, 2016)
Systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS) have an increased risk to develop cognitive impairment. A possible role for anti-phospholipid antibodies (aPL) and anti-glutamate receptor ( anti-NMDA) antibodies in the pathogenesis of neurological manifestations of these two conditions, have been suggested. In particular, the role of anti-NMDA antibodies in the pathogenesis of NPSLE is supported by several experimental studies in animal models and by the finding of a correlation between anti-NMDA positivity in CSF and neurological manifestations of SLE. However, data from the literature are controversial, as several studies have reported a correlation of these antibodies with mild cognitive impairment in SLE, but more recent studies have not confirmed this finding. The synergism between anti-NMDA and other concomitant autoantibodies, such as anti-phospholipid antibodies, can be hypothesized to play a role in inducing the tissue damage and eventually the functional abnormalities. In line with this hypothesis, we have found a high incidence of at least one impaired cognitive domain in a small cohort of patients with PAPS and SLE. Interestingly, aPL were associated with low scoring for language ability and attention while anti-NMDA titers and Mini Mental State Examination scoring were inversely correlated. However, when patients were stratified according to the presence/absence of aPL, the correlation was confirmed in aPL positive patients only. Should those findings be confirmed, the etiology of the prevalent defects found in PAPS patients as well as the synergism between aPL and anti-NMDA antibodies would need to be explored.